2005
DOI: 10.1631/jzus.2005.b0999
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of conditions for supercritical fluid extraction of flavonoids from hops (Humulus lupulusL.)

Abstract: Waste hops are good sources of flavonoids. Extraction of flavonoids from waste hops (SC-CO 2 extracted hops) using supercritical fluids technology was investigated. Various temperatures, pressures and concentrations of ethanol (modifier) and the ratio (w/w) of solvent to material were tested in this study. The results of single factor and orthogonal experiments showed that at 50 °C, 25 MPa, the ratio of solvent to material (50%), ethanol concentration (80%) resulted in maximum extraction yield flavonoids (7.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…Ethanol interacts with the flavonoids probably through noncovalent interactions and promotes a rapid diffusion into the solution (Luque de Castro and Tena 1996). Various concentration of ethanol used exhibited different effect in changing the fluid polarity and thus had diverse effect on the solubility enhancement of the flavonoids (He et al 2005). At fixed time 30 min, TFC increased with the increasing temperature (Fig.…”
Section: Total Flavonoid Content (Tfc)mentioning
confidence: 96%
“…Ethanol interacts with the flavonoids probably through noncovalent interactions and promotes a rapid diffusion into the solution (Luque de Castro and Tena 1996). Various concentration of ethanol used exhibited different effect in changing the fluid polarity and thus had diverse effect on the solubility enhancement of the flavonoids (He et al 2005). At fixed time 30 min, TFC increased with the increasing temperature (Fig.…”
Section: Total Flavonoid Content (Tfc)mentioning
confidence: 96%
“…CO 2 is abundant, inert, non-toxic, environmentally friendly solvent and acceptable in food industry. The extracts obtained by SFE are of outstanding quality and the yields are comparable with those of organic solvent extraction methods (He et al, 2005). SFE extracts were generally recognised as safe (GRAS) to be used in food products.…”
Section: Introductionmentioning
confidence: 94%
“…Chalcones, being semi-polar compounds, are extracted with a mixture of polar and non-polar solvents (Memon et al, 2014). Various methods of extraction, such as liquid solvent-based, ultrasound-assisted, pressurized liquid (Pinilla et al, 2014), soxhletion (Bimakr et al, 2011), heat reflux (Wong-Paz et al, 2014), and supercritical fluid extractions (Lien et al, 2014), are reported for maximum recoveries of flavonoids (He et al, 2005) and triterpenoids (Domingues et al, 2012) from various plants. In our present study, different conventional solvent extraction (CSE) and supercritical fluid extraction (SFE) techniques are performed and compared to achieve maximum recovery of abovementioned secondary metabolites from S. campanulatum leaves.…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose of this study is to propose a suitable quality control method for extracting these five major secondary metabolites (two flavanones, chalcone, and two triterpenoids) from S. campanulatum leaves for industrial scale applications. Furthermore, ethanol was found as a modifier because it is environmentally benign and relatively safe for human health (He et al, 2005).…”
Section: Introductionmentioning
confidence: 99%